A molecular dynamics study on the effect of surfactant adsorption on heat transfer at a solid-liquid interface. (June 2019) - Guo, Yuting; Surblys, Donatas; Kawagoe, Yoshiaki; Matsubara, Hiroki; Liu, Xiao; Ohara, Taku
Highlights: The molecular mechanism of heat transfer with surfactants at the solid surface. A dominant heat path from the solid to the solvent via surfactant molecules. Per molecule contribution to interfacial thermal conductance. Correlation of interfacial thermal conductance with interfacial potential energy. Abstract: Molecular dynamics simulations of a liquid layer between solid surfaces under a temperature gradient were performed to investigate the mechanism by which solid-liquid interfacial heat transfer is affected by adsorption of surfactant on solid surfaces with various concentrations of surfactant. The surfactant and solvent were chosen to be single-atom molecules with a contact angle of 0 and 180 degrees to the solid surface, respectively. Density distributions showed that the surfactant molecules formed a layer on the solid surface. The heat flux across the solid-liquid interface and between two adsorption layers closest to the surface was decomposed into energy transport terms based on molecular motions and inter-molecular interactions to examine the molecular mechanism of heat transfer. The interfacial thermal conductance (ITC) was also evaluated, and the molecular mechanism contributing to it was analyzed. It was found that the surfactant molecules that were adsorbed onto the solid surface decreased the interfacial thermal resistance, causing an increase in the heat flux, where the heat path from the solid to the solvent molecules via surfactant molecules became dominant as compared with the direct path from the solid to solvent molecules. It resulted in the temperature of surfactant being closer to the temperature of the solid than that of solvent in the vicinity of the solid surfaces. This indicated that in order to increase heat transfer via surfactants, not only the surfactant affinity with solid surface, but also the surfactant-solvent affinity must be considered. The contribution of each surfactant molecule to the ITC was greater than that of each solvent molecule, and both were proportional to their intermolecular potential with the solid atoms. Also, the contributions of a single surfactant and solvent molecule to the ITC were independent of their concentrations in the adsorption layer.